Structural diversity, anti-fungal activity and chemosystematics of Bornean Liverwort Bazzania harpago (De Not.) Schiffner - Ng, Shean-Yeaw; Ang, Lee-Ping; Hau, Vui-Lun; Monica Suleiman; Charles Santhanaraju Vairappan; Kamada, Takashi (Penerbit Universiti Kebangsaan Malaysia, 2021)
Two terpenes; cneorubin X (1), (-)-gymnomitr-3(15)-en-4β-ol (2) as well as one benzoic compound; caffeic acid (3) were isolated from Bazzania harpago collected from Mt. Trus Madi, Sabah, Malaysia. The structures of these secondary metabolites were elucidated based on spectroscopic data (Infra-Red (IR), 1D and 2D Nuclear Magnetic Resonance (NMR), and Mass Spectrum (MS)). This is the first record that cneorubin X (1) was isolated from non-vascular plants and it exhibited active anti-fungal activity against Haliphthoros sabahensis and Haliphthoros milfordensis. Chemosystematics finding suggests that the Marchantiophyta (liverworts) genus Bazzania might have a closer chemical relationship to its sister group Bryophyta (mosses) genus Brachythecium, Kindbergia and Mnium, as well as Anthocerophyta (hornworts) genus Anthoceros in their evolutionary history.